The history of French-speaking Protestantism in Québec - Zuidema, Jason. (Religion in the Americas, 2011)
Although French-speaking Canadians have largely been Roman Catholic, there has been a small, but significant Protestant minority among them for much of their history. Several important studies on these Protestants have appeared in French or in short articles in English, but there is no broader survey in English. Based on significant archival study, a fresh reading of printed texts and the work of a generation of historians, this collection of essays brings together the work of leading scholars in the field to bring reasoned perspective on various narratives of the history of this often forgotten religious minority. This collection highlights international and inter-confessional networks, the various stages of external and internal mission, the periods of growth and decline, and the cultural and political heritage of these Protestants.